1978
DOI: 10.1172/jci108925
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Cell Subpopulations Mediating Mitogen Hyporesponsiveness in Patients with Hodgkin's Disease

Abstract: A B S T R A C T Hodgkin's disease (HD) is associated with a deficit in T-cell immunity characterized by skin test anergy and decreased lymphocyte responses to phytohemagglutinin (PHA). To investigate this mitogen hyporesponsiveness in HD, we separated peripheral blood mononuclear cells on Ficoll-Hypaque gradients and determined their response to various suboptimal concentrations of PHA. As was expected, patients with HD demonstrated marked mitogen hyporesponsiveness relative to normal controls; however, if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Wright's stain of the peripheral blood mononuclear cell preparations revealed 96-98% mononuclear cells, 2-4% polymorphonuclear leukocytes and variable numbers of platelets. Previous work in our laboratory has demonstrated no difference between the adherent and nonadherent population in percentage of cells bearing Fc receptors, C3 receptors, surface immunoglobulin, or cells forming E-rosettes with sheep erythrocytes (11).…”
Section: Recovery Of Glass Adherent Cellsmentioning
confidence: 62%
See 1 more Smart Citation
“…Wright's stain of the peripheral blood mononuclear cell preparations revealed 96-98% mononuclear cells, 2-4% polymorphonuclear leukocytes and variable numbers of platelets. Previous work in our laboratory has demonstrated no difference between the adherent and nonadherent population in percentage of cells bearing Fc receptors, C3 receptors, surface immunoglobulin, or cells forming E-rosettes with sheep erythrocytes (11).…”
Section: Recovery Of Glass Adherent Cellsmentioning
confidence: 62%
“…These cells have been suggested as etiologic or contributory in the pathogenesis of several diseases, including common variable hypogammaglobulinemia (43), IgA deficiency (44), multiple myeloma (45), Hodgkin's disease (11,40,46), and systemic lupus erythematosus (47). Work in this area has been hindered, however, by lack of a suitable assay of suppressor cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Human T suppressor cells have been demonstrated that are both mitomycin C sensitive and resistant (32)(33)(34). Suppressive monocytes have also been demonstrated in humans and are usually mitomycin resistant (35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…Suppression by a monocytoid cell contributes to the proliferative hyporesponsiveness of lymphocytes from patients with Hodgkin's disease (16)(17)(18)(19). This abnormality is associated with an increase in the number of monocytes relative to lymphocytes in monioniuclear leukocyte (MNL)1 preparations (17).…”
Section: Introductionmentioning
confidence: 99%